The geographical efficiency of education and research: The ranking of U.S. universities. (June 2018) - Guironnet, Jean-Pascal; Peypoch, Nicolas
Abstract: This paper proposes to study the American efficiency of educational diffusion and research productivity following two distinctions: urban vs. rural areas and public vs. private universities. Following this geographical consideration, knowledge diffusion seems to be homogeneous over the American territory, whereas research productivity is more heterogeneous: American research efficiency decreased of 7% points, due to some rural university localizations. Universities in urban areas favor educational quality through high student selection criteria, contrary to those located in more rural areas. Third, public universities present higher educational efficiency, in favoring educational quality over research productivity: the lesser research efficiency of public institutions comes from difficulties in the management of several campuses, by comparison with the private institutions which are all single-campus. Highlights: This paper proposes to study both educational diffusion and research productivity from higher education. Our approach distinguishes university locations from urban vs. rural areas. Results are discussed following university status: public vs. private. Following this geographical consideration, research productivity is heterogeneous. The lesser research efficiency of public institutions comes from difficulties in the management of several campuses.